An Effective Risk Minimization Strategy Applied to an Outdoor Music Festival: A Multi-Agency Approach. Issue 2 (21st March 2018) - Luther, Matt; Gardiner, Fergus; Lenson, Shane; Caldicott, David; Harris, Ryan; Sabet, Ryan; Malloy, Mark; Perkins, Jo
Specific Event Identifiers: a. Event type: Outdoor music festival. b. Event onset date: December 3, 2016. c. Location of event: Regatta Point, Commonwealth Park. d. Geographical coordinates: Canberra, Australian Capital Territory (ACT), Australia (-35.289002, 149.131957, 600m). e. Dates and times of observation in latitude, longitude, and elevation: December 3, 2016, 11:00-23:00. f. Response type: Event medical support. Abstract Introduction: Young adult patrons are vulnerable to risk-taking behavior, including drug taking, at outdoor music festivals. Therefore, the aim of this field report is to discuss the on-site medical response during a music festival, and subsequently highlight observed strategies aimed at minimizing substance abuse harm. Method: The observed outdoor music festival was held in Canberra (Australian Capital Territory [ACT], Australia) during the early summer of 2016, with an attendance of 23, 008 patrons. First aid and on-site medical treatment data were gained from the relevant treatment area and service. Results: The integrated first aid service provided support to 292 patients. Final analysis consisted of 286 patients' records, with 119 (41.6%) males and 167 (58.4%) females. Results from this report indicated that drug intoxication was an observed event issue, with 15 (5.1%) treated on site and 13 emergency department (ED) presentations, primarily related to trauma or medical conditions requiring further diagnostics. Conclusion: This report details an important public health need, which could be met by providing a coordinated approach, including a robust on-site medical service, accepting intrinsic risk-taking behavior. This may include on-site drug-checking, providing reliable information on drug content with associated education. M Luther, F Gardiner, S Lenson, D Caldicott, R Harris, R Sabet, M Malloy, J Perkins .An effective risk minimization strategy applied to an outdoor music festival: a multi-agency approach .Prehosp Disaster Med .2018 ;33 (2 ):220 –224 .